Effect of heat on some properties of surface layer of polymeric films used for vacuum forming - Żenkiewicz, M.; Lutomirski, S. (Polimery, 2022)
The effects of specific energy of activation (Ej - controlled by speed of travel) of PP, PS or PET films, used in vacuum forming processes, on the values of contact angle, surface free energy and oxidation degree of the surface layer (WW) were presented. Contact angles with water, formamide or diiodomethane were measured by goniometer, surface free energy (SEP) was calculated using Owens-Wendt method and oxidation degree (SU) of WW was investigated using X-ray photoelectron spectroscopy (XPS). The measurements were done either after the film activation or after heating of activated film up to temperature about 150 oC and subsequent cooling to temperature about 23 oC. It was found that SEP values (Fig. 1-3) calculated on the basis of contact angles with water and diiodomethane (Table 2-4) were higher than those calculated on the basis of contact angles with formamide and diiodomethane. Heating of the films investigated decreased SEP value in every case and slightly decreased SU of WW of PP or PS (Fig. 4, 5) but not in case of PET (Fig. 6).